Understanding verbs of movement in children with autism – part 1 - Hrycyna, Ewa (Papers in Linguistics, 2024)
The aim of the article is to determine how children with autism understand selected verbs of movement. Applying the multiple case study method, the author examined three children with autism with varying levels of autistic features and varying levels of language skills who attend early education classes. The examination was preliminary in its nature. Its results revealed certain regularities regarding the understanding of verbs of movement (in their basic, literal meaning). The children were able to recognize the verb, relate it to appropriate real events, act out the semantic features of the verb and use a simple syntactic sentence pattern with it. There were, however, quantitative and qualitative differences between the children’s answers regarding particular verbs, which was described and interpreted. The quantity and quality of the children’s responses were related to the level of severity of autistic features and their direct correspondence to the Diagnostic and Statistical Manual of Mental Disorders criteria and the level of language skills.